2021
DOI: 10.1186/s41231-020-00081-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of serotonin and diet in the prevalence of irritable bowel syndrome: a systematic review

Abstract: Serotonin or 5-hydroxytryptamine (5-HT)- a neurotransmitter of both the Enteric Nervous System and the Central Nervous System is synthesized by the hydroxylation of L- tryptophan to 5-hydroxytryptophan.Serotonin has been associated with gut functions like assimilation and absorption, alongside the regulation of particle transport and fluid discharge in the gastrointestinal tract and its deficiency is found to be a prominent factor in the prevalence of gut disorders like Irritable Bowel Syndrome.For this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Enteric microbiota play a critical role in regulating a variety of neurotransmitters, including histamine, serotonin (5-hydroxytryptamine, 5-HT), glutamate, γ-aminobutyric acid (GABA), dopamine, acetylcholine, and catecholamines [ 18 , 22 , 24 ], and each biological substance influences the activity of the enteric nervous system (ENS) independently or corporately as part of the pathology of IBS [ 22 , 25 ]. Among those, 5-HT is one of the most well-studied neurotransmitters in IBS research investigations [ 26 , 27 , 28 ]. Enteric 5-HT boosts visceral hypersensitivity, increases mucosal permeability, alters gut motility, activates the immune system, and induces inflammation, which synergistically contribute to forming IBS symptoms [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enteric microbiota play a critical role in regulating a variety of neurotransmitters, including histamine, serotonin (5-hydroxytryptamine, 5-HT), glutamate, γ-aminobutyric acid (GABA), dopamine, acetylcholine, and catecholamines [ 18 , 22 , 24 ], and each biological substance influences the activity of the enteric nervous system (ENS) independently or corporately as part of the pathology of IBS [ 22 , 25 ]. Among those, 5-HT is one of the most well-studied neurotransmitters in IBS research investigations [ 26 , 27 , 28 ]. Enteric 5-HT boosts visceral hypersensitivity, increases mucosal permeability, alters gut motility, activates the immune system, and induces inflammation, which synergistically contribute to forming IBS symptoms [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence revealed that the decrease in intestinal serotonin leads to weakness in the intestinal lining, which inevitably results in constipation and an increase in serotonin levels within the gut [ 37 ]. Another hypothesis in this context implies the deficiency of the serotonin transporter‐serotonin reuptake transporter (SERT) enterocytes in IBS patients [ 38 ]. Indeed, serotonin, which is regulated by SERT, could influence gut distension, motility and visceral sensitivity [ 39 ].…”
Section: Potential Pathways That Link Pcos and ...mentioning
confidence: 99%
“…Peripheral serotonin (5-HT) (80%-90% of the total body content of serotonin) is synthesized in the gut predominately by the enterochromaffin cells (ECs) from tryptophan-by-tryptophan hydroxylase 1 (Tph1) [32][33][34][35]. Interestingly, the release of 5-HT from the ECs, the most abundant enteroendocrine cell subtype of the colon [36], is under the control of the autonomous nervous system [37].…”
Section: Sna Enterochromaffin Cells (Ecs) Peripheral Serotonin (5-ht)...mentioning
confidence: 99%